Covid-19 air travel: do intervention measures influence intent? - Montalbo, Kyle Calapre (Institut Pariwisata dan Bisnis Internasional, 2022)
Similar to the 9/11 terrorist attacks in 2002, safety measures in air travel are placed to combat the spread of COVID-19. With developing countries, like the Philippines, lagging behind post-pandemic aviation recovery, just how influential are these intervention measures in bringing back travellers to the skies? This research measured the passengers’ intent to return to air travel and analyzed the respondents’ assessment of the implementation of safety measures in air travel during the COVID-19 pandemic. The correlation of both variables was explored using Pearson Correlation Coefficient. The data were from a self-administered survey questionnaire disseminated to air travellers to and from Mactan Cebu International Airport (MCIA), Philippines during the COVID-19 pandemic. The results show that the safety protocols were far from being exceptionally implemented. The study further revealed the respondents’ uncertainty on returning to air travel due to the COVID-19 crisis regardless of the safety measures in place. Even with the high uncertainty, however, the respondents’ assessment of the implementation of protocols was found to be highly associated with the respondents’ intention to return to air travel. The pre-departure safety protocols had the highest association compared to in-flight and arrival protocols.